High gastrointestinal bleeding and duodenal occlusion as a complication of peritoneal hidatic disease - Pittamiglio, Horacio; Tchekmedyian, Vartan; Castro, Danilo; Santana, Carlos; Plaván, María (Cirugía del Uruguay, 1983)
A rare complication of peritoneal hidatic disease associated to other pathological entity, which are eth iological related, is presented. The tests, diagnosis and therapeutic conduct adopted are described.